Comparison of water-caprock and CO2-water-caprock geochemical reactivity in the Triassic Heshanggou Formation of Ordos Basin. (March 2023) - Ma, Xin; Diao, Yujie; Fu, Lei; Yan, Jing; Yang, Guodong; Zhang, Chenglong; Liu, Siyu; Dong, Hanchuan; Yu, Ying
Highlights: Dissolution occurring in caprock after long-term water-rock interactions without CO2 injection. Self-sealing capability of caprock is enhanced under the condition of CO2 injection with a maximum decrease of 40% in permeability. Dolomite, siderite, magnesite and dawsonite are the key CO2 trapping minerals for the enhancement of caprock sealing. The dissolution of albite, chlorite and calcite provides the necessary Na +, Mg 2+, Ca 2+ and Fe 2+ for the precipitation of carbonate minerals. Abstract: This study investigates the influence of geochemical reactions among CO2, water and key minerals on caprock sealing using laboratory experiments and numerical simulations, based on mudstone caprock of the Triassic Heshanggou Formation at the Shenhua CCS demonstration project in Ordos Basin. The results show that there is an obvious dissolution occurring in caprock after long-term water-rock interactions without CO2 injection, with a maximum increase of 11% in caprock permeability. The dissolution of kaolinite, chlorite, K-feldspar and quartz results in the increase of caprock permeability, and the precipitation of illite and hematite is the key factor effectively slowing down the change of permeability. However, the self-sealing capability of the caprock is continuously enhanced under the condition of CO2 injection, with permeability reduced by 40% of the original permeability at maximum. The precipitation of carbonate minerals directly induces the change of caprock permeability, and the precipitation of Ca-smectite and quartz further promotes the caprock sealing. Dolomite, siderite, magnesite and dawsonite are the key CO2 trapping minerals for the enhancement of caprock sealing, and the maximum amount of CO2 trapped in mineral phase is 35.44 kg/m 3 medium. The dissolution of albite, chlorite and calcite provides the necessary Na +, Mg 2+, Ca 2+ and Fe 2+ for the precipitation of carbonate minerals, which is conducive to the enhancement of caprock sealing, while chlorite and calcite are the key minerals affecting the caprock sealing. The dissolution of K-feldspar is not conducive to the enhancement of caprock sealing. This study could provide a theoretical basis for selection of reservoir-caprock and safety evaluation of CO2 geological storage. Graphical abstract: Image, graphical abstract